CD1d expression as a prognostic marker for chronic lymphocytic leukemia. Issue 2 (February 2014) - Anastasiadis, Athanasios; Kotsianidis, Ioannis; Papadopoulos, Vasileios; Spanoudakis, Emmanouil; Margaritis, Dimitrios; Christoforidou, Anna; Gouliamtzi, Stamatoula; Tsatalas, Costas
Abstract We analyzed the expression of CD1d, an antigen-presenting molecule, on peripheral blood leukemic cells of cases of chronic lymphocytic leukemia (CLL) by flow cytometry. We demonstrated variable expression of CD1d on leukemic lymphocytes and an association between high expression of CD1d with shorter time to treatment and overall survival of patients. CD1d was positively associated with CD38 expression, but not with unmutated heavy chain variable (VH) mutational status or adverse cytogenetics of leukemic lymphocytes. Our findings support that CD1d expression is a prognostic marker for CLL.